Big Picture Mental Health of Generation Z in The World - Akbar, Bintang Mukhammad Burhanudin; Prawesti, Dini Rahma Dwi; Perbani, Wikan Swadesi Arum (Jurnal Kesehatan Komunitas Indonesia, 2024)
Background: Mental health problems, especially in Generation Z, are currently an important issue to be addressed. Purpose: This condition is caused by mental health being able to influence various aspects of life. Methods: This research method uses a Systematic Literature Review approach with the Prisma protocol, which focuses on five continents. Results: The research results explained that there was an increase in cases of depression, anxiety, stress, and sleep disorders in Generation Z. This was influenced by several factors, such as excessive exposure to information on social media, fatigue from using social media, as well as academic stressors and social problems faced. Conclusion: Handling mental health problems can be done by providing mental health education, psychotherapy, social support, and managing the use of social media and gadgets.